33 CRISCO-UGIS: COMPOSITE RISK SCORE TO PREDICT POST-OPERATIVE COMPLICATIONS FOR UPPER GASTROINTESTINAL CANCER SURGERY. (14th September 2020) - Kammili, A; Trépanier, M; Naghawi, H; Cools-Lartigue, J; Mulder, D; Ferri, L; Mueller, C
Abstract: : Gastroesophagectomy for cancer is associated with high risk of morbidity and mortality. Careful patient selection for surgery is essential for optimizing outcomes. The purpose of this study was to develop a reliable composite risk calculator to inform pre-operative decision-making using readily available patient and tumour characteristics. Methods: Patients undergoing curative-intent resection for gastroesophageal cancer from January 2010 to December 2018 were identified from a prospectively collected database. Data were verified and collected from patients' medical records. Multiple logistic regression modeling identified pre-operative variables associated with significantly elevated risk of moderate to severe post-operative complications (Clavien-Dindo score ≥ 2) within 30 days of surgery and a nomogram was developed to form the composite risk score (CRiSCo-UGIS). Internal model validation was performed. Results: Among 520 patients, independent pre-operative risk factors for complications were: female sex, age-adjusted Charlson comorbidity index ≥5, albumin <35 g/L, proximal tumour location (esophagus and gastroesophageal junction) and reduced performance status (Eastern Cooperative Oncology Group performance status 2–3) (Table 1). CRiSCo-UGIS had a good model fit (Hosmer-Lemeshow p = 0.47, area under receiver operating characteristic curve = 0.69). The overall observed-to-expected ratio was 1.0 [95% confidence interval 0.9–1.1]. Patients were divided into low (0), moderate (1–2) and high (≥3 points) risk categories. The observed risk of complications was: 42% in low-risk, 53% in moderate-risk and 80% in high-risk. Conclusion: CRiSCo-UGIS can reliably predict post-operative complications for gastroesophageal cancer resection based on readily available pre-operative characteristics. This composite score can be used to guide patient selection for surgery and enhance informed consent discussions.